-8h+18=-10h

Simple and best practice solution for -8h+18=-10h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8h+18=-10h equation:


Simplifying
-8h + 18 = -10h

Reorder the terms:
18 + -8h = -10h

Solving
18 + -8h = -10h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '10h' to each side of the equation.
18 + -8h + 10h = -10h + 10h

Combine like terms: -8h + 10h = 2h
18 + 2h = -10h + 10h

Combine like terms: -10h + 10h = 0
18 + 2h = 0

Add '-18' to each side of the equation.
18 + -18 + 2h = 0 + -18

Combine like terms: 18 + -18 = 0
0 + 2h = 0 + -18
2h = 0 + -18

Combine like terms: 0 + -18 = -18
2h = -18

Divide each side by '2'.
h = -9

Simplifying
h = -9

See similar equations:

| X=ln21/ln8 | | 3k+m=10 | | 1+2c=4c+19 | | 5-3(4-2x)+3-2(5-x)=0 | | 4/5k=5/2 | | -8t=-13+20 | | Kx-k=1 | | -18m+1=-m+20-18m | | 23x+1=22x+4 | | -14-8n=18-16n | | 4s=-10+5s | | -3v-5=6v-5 | | 9+2z+9z=-1+10z | | -3d=-8-7d | | 2w+6=-2-10 | | 2(x-1)-3(3x+2)+4(x+2)=0 | | -2y+5+3y=5y+5 | | .5b+4=20 | | -10-5g=8+4g | | 5(2l+3)=95 | | 10j+2=9j+10 | | (x+19)=(7x-8) | | q=9+2q | | 5k+9=4K | | -2k+4m=-9 | | 10u-3=9u-6 | | 7f-8=6f | | 5x+y+4x-y=360 | | -0.146x^2+0.96x+7.5=0 | | 4x-y=55 | | s=2cos(0) | | -26+7p=2(7p-6) |

Equations solver categories